Al-Qur’an sebagai Sumber Ilmu Pengetahuan (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2022)
The peak era of Islam's glory in the classical period was marked by the development of knowledge in the form of science, theology, philosophy, hadith, the Koran and other sciences. The success did not last long because it was displaced by western civilization and the colonialism and Sufism movements of the Muslim community itself which made Islam decline. Then there was Ziauddin Sardar, an Islamic thinker who was present who wanted to reconcile Western and Eastern civilization with the ideas of Islamic knowledge. This research aims to find out that the Koran is a source of knowledge. This research uses qualitative research methods with the type of library research. The data in this research uses primary data and secondary data. Then analyzed using the tahlili method and content analysis method to achieve the research objectives. After carrying out all the research processes, it can be seen that the letter Al-'Alaq, which is the first revelation, is basically a command to pay attention to science, which contains three aspects, namely the value of skills education, the value of divine education, and the value of intellectual education.